2002
DOI: 10.1164/ajrccm.165.6.2101049
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Reduces Lipopolysaccharide-induced Lethal Toxicity and Expression of Proinflammatory Molecules in Mice

Abstract: Luteolin is a flavonoid that has been shown to reduce proinflammatory molecule expression in vitro. In the present study, we have tested the ability of luteolin to inhibit lipopolysaccharide (LPS)- induced lethal toxicity and proinflammatory molecule expression in vivo. Mice receiving LPS (Salmonella enteriditis LPS, 32 mg/kg, intraperitoneally) exhibited high mortality with only 4.1% of the animals surviving seven days after the LPS challenge. On the contrary, mice that had received luteolin (0.2 mg/kg, intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 30 publications
5
94
1
3
Order By: Relevance
“…According to Comalada et al (2006), luteolin is able to stimulate the expression of the antiinflammatory cytokine IL-10. In addition, luteolin inhibits LPS-induced IjB phosphorylation and TNFa secretion by macrophages in vitro and has antiinflammatory activities in mice (Kim and Jobin 2005;Kotanidou et al 2002). In contrast to these findings, our results showed that luteolin had no inhibitory effects on IjB signal expression.…”
Section: Discussioncontrasting
confidence: 98%
“…According to Comalada et al (2006), luteolin is able to stimulate the expression of the antiinflammatory cytokine IL-10. In addition, luteolin inhibits LPS-induced IjB phosphorylation and TNFa secretion by macrophages in vitro and has antiinflammatory activities in mice (Kim and Jobin 2005;Kotanidou et al 2002). In contrast to these findings, our results showed that luteolin had no inhibitory effects on IjB signal expression.…”
Section: Discussioncontrasting
confidence: 98%
“…Therefore, it is theoretically reasonable to target IL-6/STAT3 to intervene in the early stage of autoimmune thyroiditis in order to explore novel therapeutic strategies for HT. Previous studies have shown that luteolin has potent anti-inflammatory effects in vitro and in vivo (38,39) and the mechanisms involved include the activation of NF-κB, which leads to the expression of IL-6 and COX-2 (18,40). Activator protein-1 (AP-1) is also an important transcription factor associated with immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…iNOS Suppresses iNOS expression [33], [35], [34], [43], [81], [82], [84] NO Supresses NO production [33], [35], [48], [34], [43], [56], [81] PGD-2 Inhibits PGD-2 release from human mast cells [51], [52] Leukotrienes Inhibits leukotriene release from human mast cells [51], [52] Leukotriene B4 inhibits LT B4 synthesis [87] Leukotriene C4 No effect [37] Thromboxane B2 Inhibits TX B2 synthesis [87] Histamine Inhibits histamine release from human mast cells [51], [52] GM-CSF Inhibits GM-CSF release from human mast cells [51], [52] TNF-α Suppresses TNF-α expression [48], [34], [36], [42], [53], [55], [56], [81], [93] COX-2 Suppresses COX-2 expression [28], [57], [81], [84] NFκB Inhibits DNA binding and transcription [32], [35], [36], [81], [82] NFκB Does not inhibit NFκB nuclear translocation, DNA binding or phosphorylation but inhibits transcription [85] AP-1 Induces AP-1 DNA binding <...>…”
Section: Effect Of Luteolin Publication Source(s)mentioning
confidence: 99%